The unexpected Christian century : the reversal and transformation of global Christianity, 1900-2000 - Sunquist, Scott W. (Scott William), 1953-; Noll, Mark A., 1946- (Grand Rapids, MI : Baker Academic, 2015)
In 1900 many assumed the twentieth century would be a Christian century because Western "Christian empires" ruled most of the world. What happened instead is that Christianity in the West declined dramatically, the empires collapsed, and Christianity's center moved to Africa, Asia, Latin America, and the Pacific. How did this happen so quickly? Sunquist surveys the most recent century of Christian history, highlighting epochal changes in global Christianity. He also suggests lessons we can learn from this remarkable global Christian reversal
Includes bibliographical references and index
Keywords: Church history -- 20th century